PRINSIP-PRINSIP BELAJAR DALAM PERSPEKTIF PSIKOPEDAGOGIK ISLAM: ANALISIS KONSEPTUAL DAN IMPLIKASI PEMBELAJARAN MODERN - Sumiati Gusri; Afnibar; Ulfatmi (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to analyze the principles of learning from the perspective of Islamic psychopedagogy and their implications for modern educational practice. The research employs a qualitative descriptive method with a library research approach, examining classical Islamic literature and contemporary educational psychology theories. The results reveal that the learning principles in Islam such as readiness (al-isti‘dad), motivation (al-dafi‘), experience (al-tajribah), and repetition (al-tikrar) demonstrate substantial convergence with behaviorist, cognitive, and constructivist theories. Effective learning occurs when teachers nurture spiritual awareness, intrinsic motivation, and active learner participation. These principles highlight the integration of spiritual and rational dimensions within learning. Thus, Islamic psychopedagogy provides both normative and scientific foundations for developing holistic, character-based, and human-centered education.